A climatic environmental performance assessment method for ecological city construction: Application to Beijing Yanqi Lake - Xiao-Yi Fang (Advances in Climate Change Research, 2015)
In contrast to the input perspective for evaluating planning metrics, this research takes the climatic environmental output effects as the starting point for assessing ecological city construction. Based on approaches such as observation data analysis, meteorological model simulation, and remote sensing, a set of climatic environmental performance assessment methods is developed and established. These methods mainly focus on surface ventilation assessment and urban thermal environment assessment. With the Yanqi Lake ecological development demonstration area located in Huairou district, Beijing as an example, the assessment of the local climatic environment before and after the construction are conducted, and relevant policy suggestions for urban planning and construction are presented. The results show that after development, the ventilation capacity will decrease overall and the ventilation potential index will decrease from 0.53 to 0.44. While this is not a large reduction, and is still at a favorable level, the ventilation potential in some local areas will markedly decrease. Furthermore, the thermal environment will become poorer to some extent; the urban heat island (UHI) area and intensity will increase compared with the current situation; continuous heat islands may occur in local areas; the UHI potential index of the core area will rise from 0.0878 to 0.1217 (still a favorable level). Therefore, urban surfaces should be carefully developed and arranged during planning. It is suggested that the negative impacts of large areas of urban construction on the local climatic environment in the Yanqi Lake could be mitigated by 1) strengthening the airflow by introducing fresh, cold, northwesterly air via constructed ventilation corridors, 2) increasing the number of ecological cold sources, particularly for water bodies and green belts to prevent the UHI in the southern region of Yanqi Lake from becoming linked with each other, and 3) considering a pre-program before sub-domain and building planning to obtain optimum building locations. Different construction standards should be developed for different ventilation potential and UHI intensity levels. For strong heat island areas, land areas should be reserved to serve as cold sources.